Renewable energy in chemical industrial buildings for cost performance - Kussumardianadewi, Bernadette Detty; Husin, Albert Eddy; Sinaga, Lastarida (SINERGI, 2025)
Due to their potential benefits for a variety of industries, blockchain technologies have recently attracted a lot of attention from the scientific community as well as the business community. Blockchain provides distributed, secure, permissioned transactional ledgers, that successfully deal with these problems. The purpose of this study is to present a new conceptual framework that combines blockchain technology with building information modeling. This framework is specifically designed for smart contracts and digital transactions in the chemical industry's retrofitting of green buildings. Within this particular context, the main goals are to improve cost-effectiveness, bolster cybersecurity measures, improve information sharing and management, expedite payment transactions, and advance sustainability. In Cilegon, Banten, Indonesia, a chemical facility was the study's location. The study also makes use of partial least squares structural equation modeling.